Evaluation of Fe-nitrides, -borides and -carbides for enhanced magnetic fluid hyperthermia with experimental study of α″-Fe16N2 and ϵ-Fe3N nanoparticles. (12th January 2023) - Dirba, I; Chandra, C K; Ablets, Y; Kohout, J; Kmječ, T; Kaman, O; Gutfleisch, O
Abstract: In this work, we investigate alternative materials systems that, based on their intrinsic magnetic properties, have the potential to deliver enhanced heating power in magnetic fluid hyperthermia. The focus lies on systems with high magnetization phases, namely iron-nitrogen (Fe-N), iron-boron (Fe-B) and iron-carbon (Fe-C) compounds, and their performance in comparison to the conventionally used iron oxides, γ -Fe2 O3, Fe3 O4 and non-stoichiometric mixtures thereof. The heating power as a function of the applied alternating magnetic field frequency is calculated and the peak particle size with the maximum specific loss power (SLP) for each material is identified. It is found that lower anisotropy results in larger optimum particle size and more tolerance for polydispersity. The effect of nanoparticle saturation magnetization and anisotropy is simulated, and the results show that in order to maximize SLP, a material with high magnetization but low anisotropy provides the best combination. These findings are juxtaposed with experimental results of a comparative study of iron nitrides, namely α ″-Fe16 N2 and ϵ -Fe3 N nanoparticles, and model nanoparticles of iron oxides. The former ones are studied as heating agents for magnetic fluid hyperthermia for the first time.